THE DEPENDENCE OF WOOL PRODUCTIVITY OF CAMELUS DROMEDARIUS ON PASTURE AREAS IN THE USTYURT PLATEAU (British Journal of Global Ecology and Sustainable Development, 2026)
This article investigates the relationship between the wool productivity of dromedary (single-humped) camels and their pasture areas in the conditions of the Ustyurt Plateau. It presents the observed variations in wool productivity and provides conclusions based on the findings.